2022
DOI: 10.1155/2022/6833078
|View full text |Cite|
|
Sign up to set email alerts
|

C-Reactive Protein as a Prognostic Biomarker for Gynecologic Cancers: A Meta-Analysis

Abstract: Background. The prognostic role of CRP (C-reactive protein) in gynecological tumors has been previously reported in individual studies, but whether CRP can be used as a separate potential prognostic factor has not been systematically reviewed. The purpose of this research is to determine if there is a link between CRP levels and the prognosis of gynecological cancer patients. Methods. A systematic search was carried out to find the literature evaluating the predictive role of CRP in the prognosis of gynecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…CRP testing is noninvasive, easy to detect, inexpensive, repeatable, and can track tumor status in real time, making it a hot topic in the emerging field of noninvasive tumor markers. Various meta-analyses have shown that CRP has significant prognostic value for solid tumors, including gynecological tumors ( 24 ), urinary tract tumors ( 25 ), lung cancer ( 26 ), and colorectal cancer ( 27 ). Additionally, CRP is associated with low OS in various tumors, consistent with the results of this meta-analysis, which showed that CRP was associated with low OS in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…CRP testing is noninvasive, easy to detect, inexpensive, repeatable, and can track tumor status in real time, making it a hot topic in the emerging field of noninvasive tumor markers. Various meta-analyses have shown that CRP has significant prognostic value for solid tumors, including gynecological tumors ( 24 ), urinary tract tumors ( 25 ), lung cancer ( 26 ), and colorectal cancer ( 27 ). Additionally, CRP is associated with low OS in various tumors, consistent with the results of this meta-analysis, which showed that CRP was associated with low OS in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis found that CRP can be used as a possible prognostic indicator for a variety of gynecologic malignancies, such as cervical cancer, ovarian cancer, endometrial cancer, and vulvar cancer [ 839 ]. Yet, a study found that CRP combined with other markers could be beneficial to distinguish leiomyosarcoma from especially degenerated or atypical leiomyoma [ 840 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%
“…The uterine immune cell number changes cyclically with the menstrual cycle and inflammatory insult. Chronic inflammation without resolution may induce cancer, including endometrial cancer (EC), and systemic inflammatory markers, including C-reactive protein (CRP), serve as prognostic markers [99][100][101]. Hence, systemic and local inflammation may affect predisposition to the EC and its severity.…”
Section: Nk Cells In the Uc Immune Microenvironment (Ucim)mentioning
confidence: 99%